Don't Have a Cow, Man: Consumer Acceptance of Animal-Free Dairy Products in Five Countries - Zollman Thomas, Oscar; Bryant, Christopher (Frontiers in Sustainable Food Systems, 2021)
Concern with the ethical, environmental and health consequences of the livestock industry is pushing the growth of a sector of animal-free alternatives. Advancing research is allowing these products to increasingly deliver experiences on a par with and beyond the products they originally sought to emulate, but widespread consumer adoption has not yet been realised. This research surveyed 5,054 individuals from Brazil, Germany, India, the UK and the USA, examining the nature and extent of acceptance of dairy products derived from precision fermentation, one of the three main pillars of alternative proteins. We find substantial consumer acceptance across countries for these products, animal-free dairy cheese, seeing 78.8% of consumers as probably or definitely likely to try such a product, with 70.5% probably or definitely likely to buy, substantially higher than previous research has found for cultivated meat products. Consumers anticipated animal-free dairy cheese to be significantly more tasty than current vegan cheese products, and just as tasty and safe as basic animal-derived cheese while rating it as significantly more ethical and environmentally friendly. Multiple linear regression revealed that within dietary identifiers, vegetarianism and veganism were strong predictors of willingness to buy but flexitarianism showed the strongest predictive power for willingness to buy. Of all variables, the strongest predictor of willingness to buy was current level of cheese consumption. Further regressions revealed that taste perception was key to driving purchase intent across all countries. The implications of these results for the development of the animal-free dairy sector are discussed.